Label-Free Quantitative Proteomics Unravel the Impacts of Salt Stress on Dendrobium huoshanense - Song, Cheng; Zhang, Yunpeng; Chen, Rui; Zhu, Fucheng; Wei, Peipei; Pan, Haoyu; Chen, Cunwu; Dai, Jun (Frontiers in Plant Science, 2022)
Salt stress is a constraint on crop growth and productivity. When exposed to high salt stress, metabolic abnormalities that disrupt reactive oxygen species (ROS) homeostasis result in massive oxygen radical deposition. D. huoshanense is a perennial orchid herb that thrives in semi-shade conditions. Although lots of studies have been undertaken on abiotic stresses (high temperature, chilling, drought, etc.) of model plants, few studies were reported on the mechanism of salt stress in D.huoshanense. Using a label-free protein quantification method, a total of 2002 differential expressed proteins were identified in D.huoshanense. The Kyoto Encyclopedia of Genes and Genomes (KEGG )enrichment indicated that proteins involved in vitamin B6 metabolism, photosynthesis, spliceosome, arginine biosynthesis, oxidative phosphorylation, and MAPK signaling were considerably enriched. Remarkably, six malate dehydrogenases (MDHs) were identified from deferentially expressed proteins. (NAD+)-dependent MDH may directly participate in the biosynthesis of malate in the nocturnal crassulacean acid metabolism (CAM) pathway. Additionally, peroxidases such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as antioxidant enzymes involved in glutathione biosynthesis and some vitamins biosynthesis were also identified. Taken together, these results provide a solid foundation for the investigation of the mechanism of salt stress in Dendrobium spp.